2000
DOI: 10.1074/jbc.275.16.11852
|View full text |Cite
|
Sign up to set email alerts
|

p300 and p300/cAMP-responsive Element-binding Protein Associated Factor Interact with Human T-cell Lymphotropic Virus Type-1 Tax in a Multi-histone Acetyltransferase/Activator-Enhancer Complex

Abstract: The human T-cell lymphotropic virus, type (HTLV)-1 trans-activator, Tax, coordinates with cAMP-responsive element-binding protein (CREB) and the transcriptional co-activators p300/CBP on three 21-base pair repeat elements in the proviral long terminal repeat (LTR) to promote viral mRNA transcription. Recruitment of p300/CBP to the activator-enhancer complex, however, is insufficient to support Tax-dependent LTR trans-activation. Here, we report that the p300/CBP-associated factor (P/CAF) is a critical and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 65 publications
(85 reference statements)
7
114
0
Order By: Relevance
“…Our studies demonstrate that CBP and p300, but not PCAF, enhance Tax-2-directed LTR transactivation. The fact that PCAF, p300, and CBP all are essential for optimal transactivation by Tax-1 (23)(24)(25) substantiates the existence of important differences between HTLV-2 Tax-2 and HTLV-1 Tax-1. The different requirement for PCAF between the two viral transactivators also implies that Tax-1, but not Tax-2, might influence nuclear PCAF-containing complexes, potentially contributing to the pleiotropic deregulated expression of cellular genes during leukemogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our studies demonstrate that CBP and p300, but not PCAF, enhance Tax-2-directed LTR transactivation. The fact that PCAF, p300, and CBP all are essential for optimal transactivation by Tax-1 (23)(24)(25) substantiates the existence of important differences between HTLV-2 Tax-2 and HTLV-1 Tax-1. The different requirement for PCAF between the two viral transactivators also implies that Tax-1, but not Tax-2, might influence nuclear PCAF-containing complexes, potentially contributing to the pleiotropic deregulated expression of cellular genes during leukemogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…This interaction stabilizes the complex and facilitates the recruitment of general transcription factors and coactivators, such as the histone acetyltransferases (HATs), CBP, p300, and p300͞CBP-associated factor (PCAF), resulting in the enhancement of transcription (21)(22)(23)(24)(25)(26). Tax-1 also deregulates the expression of a variety of cellular genes and signaling pathways involved in cell cycle progression, cell growth, DNA repair, and apoptosis.…”
mentioning
confidence: 99%
“…Tax does not directly bind DNA, but associates through its N-terminus with the CREB protein (Baranger et al, 1995;Adya and Giam, 1995), which docks at the LTR's cyclic-AMP responsive (CRE)-motifs. Tax also recruits transcriptional coactivators, CBP and p300 (Giebler et al, 1997;Bex et al, 1998;Harrod et al, 2000), and in a lessdefined manner, P/CAF (Okada and Jeang, 2002). The C-terminal activation domain of Tax (Semmes and Jeang, 1995) is thought to directly contact the TATAbox-bound TBP protein (Caron et al, 1993) thereby promoting transcriptional initiation and RNA polymerase elongation (Ching et al, 2004).…”
Section: Structure-function Features Of Tax For Transcriptional Activmentioning
confidence: 99%
“…Recent data have also indicated that the PI3K-Akt pathway in the interaction with CREB/ATF-1 (1, 8,152,199,204,205), CBP/p300 (12,58,59,99,106), and the Tax-responsive 21-bp repeat element, and activates the NF-!B pathway (26,44,82,178,187,194). In addition to its transactivation functions, Tax also impacts on many aspects of the cell cycle (90,96,108,111,112,118,145).…”
Section: Nf-!b Activation By Tax Is Not Sufficient For the Transformamentioning
confidence: 99%
“…The HTLV-1 viral transactivator/onco-protein Tax is thought to play an important role in T-cell malignancy and HAM/TSP. Tax transactivates the HTLV-1 LTR promoter through its interaction with CREB/ATF-1 (1, 8,152,199,204,205), CBP/p300 (12,58,59,99,106), and the Tax-responsive 21-bp repeat element, and activates the NF-!B pathway (26,82,178,187,192,194) through the interaction with PP2A/IKK" (44). In addition to its transactivation functions, Tax also impacts on many aspects of the cell cycle: activating G 1 /S transition (90,118,145), inactivating p53 functions (158), inducing p21 CIP1/WAF1 mRNA transcription (2,24,33,89), and inhibiting apoptosis and DNA repair (87,104).…”
Section: Introductionmentioning
confidence: 99%